The effect of myocardial fibrosis on left ventricular torsion and twist in patients with non-ischemic dilated cardiomyopathy - (:unkn) unknown (VIA MEDICA, 2013)
Background: Left ventricular (LV) rotation, twist, and torsion are important aspects of the cardiac performance. Myocardial fibrosis can be identified as the late gadolinium enhancement (LGE) in cardiac magnetic resonance (CMR). In this study, we investigated the association between myocardial fibrosis and LV rotational parameters in patients with nonischemic dilated cardiomyopathy (NDC). Methods: Twenty-two NDC patients were enrolled. LV dimensions, volumes and ejection fraction (EF) were measured, conventional tissue Doppler imaging data was acquired. Speckle tracking imaging was performed to measure LV deformation, LV rotational parameters. Blood samples were obtained for NT-proBNP. Late gadolinium enhanced cardiac magnetic resonance (LGE-CMR) was used to assess cardiac fibrosis index. Results: Myocardial deformation was similar between LGE+ and LGE-groups. LGE+ patients have significantly higher basal and lower apical systolic rotation, lower twist and torsion when compared to LGE-patients. However, untwisting rate was similar between the groups. Torsion was significantly correlated with LVEF and MR-index. Patients with reversed apical systolic rotation had significantly greater NT-proBNP values, basal systolic rotation and significantly lower apical systolic rotation, torsion, and MR-index. Conclusions: Cardiac fibrosis index is closely related with myocardial torsion and LV systolic function and may be used for the evaluation of cardiac condition. Reversed apical systolic rotation indicated more extensive cardiac fibrosis as it may reflect severe LV dyssynchrony and poor LV performance.
Keywords: dilated cardiomyopathy; magnetic resonance; echocardiography; CARDIOVASCULAR MAGNETIC-RESONANCE; SPECKLE TRACKING ECHOCARDIOGRAPHY; HEART-FAILURE; EJECTION FRACTION; APICAL ROTATION; VALIDATION; DEFORMATION; DYSFUNCTION; PROGNOSIS; OUTCOMES